Implementasi dan Perkembangan Halal Tourism pada Destinasi Pariwisata Lombok - Joseph Aldo Irawan; Novi Khotimah; Era Putri Amazta Fardah; Akmal Triyas Adhiprastha; Vanya Shalma Rachmie Putri (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Lombok has long been touted as a "new Bali" tourism destination. Along with the changing times, changes in tourist trends also develop and begin to recognize various new types of tourism. Lombok has a uniqueness that is thick with Islamic nuances. Therefore, Lombok applies a type of Muslim-friendly tourism / halal tourism. Muslim-friendly tourism types have been implemented indirectly by tourism actors in Lombok. Visits to various tourism destinations in Lombok were taken as samples representing the city. With qualitative descriptive research methods, the author wants to present observations supported by exposure to documentation and interviews. The author also bases research on a theory tested in reality, especially in Lombok tourism destinations. Based on the study results, several Lombok tourism destinations still need help implementing Muslim-friendly tourism. Problems are known both from destination location factors and market segmentation factors. However, some locations have been found to have long-term development opportunities that make it possible to implement Muslim-friendly tourism as a whole through certain efforts. The fulfillment of the minimum requirements for Muslim-friendly tourism does not have a coercive nature but has the opportunity to influence tourists' interest in visiting. Therefore, the Lombok government, with Muslim-friendly tourism branding together with stakeholders, maintains and improves the quality of tourism services for the sustainability of Lombok's tourism economy.